Ba4Ti13O30 nanocrystals prepared by hydrothermal method. Issue 1 (13th November 2019) - Li, Shaoqing; Li, Xinyi; Zou, Kai; Huang, Zhixiong; Zhang, Lianmeng; Guo, Dongyun; Ju, Yang
Abstract: The Ba4 Ti13 O30 nanocrystals were synthesized by a hydrothermal method. The Ba‐Ti precursor was prepared by mixing barium acetate and bis(ammonium lactate) titanium dihydroxide in deionized water with NaOH pH‐adjusting agent. In the Ba‐Ti precursor, NaOH concentration was 2.0 mol/L, and the concentrations of Ba 2+ and Ti 4+ ions were 0.023 and 0.077 mol/L, respectively. As the Ba‐Ti precursor was heated in the autoclave at 260°C for 20 hours with vigorous stirring, the single‐crystalline Ba4 Ti13 O30 nanocrystals were successfully synthesized. Abstract : The single‐crystalline Ba4 Ti13 O30 nanocrystals were successfully synthesized by a hydrothermal method. The Ba‐Ti precursor was prepared by mixing barium acetate and bis(ammonium lactate) titanium dihydroxide in deionized water with the NaOH pH‐adjusting agent. In the Ba‐Ti precursor, NaOH concentration was 2.0 mol/L, and the concentrations of Ba 2+ and Ti 4+ ions were 0.023 and 0.077 mol/L, respectively. As the Ba‐Ti precursor was heated in the autoclave at 260°C for 20 hours with vigorous stirring, the single‐phase Ba4 Ti13 O30 nanocrystals were formed.